2011
DOI: 10.1007/s00330-011-2335-8
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-based prediction of the coagulation zone in sequential temperature mapping in MR-guided radiofrequency ablation of liver tumours

Abstract: • Temperature monitoring can be used to survey MR-guided radiofrequency ablation • The developing ablation zone can be estimated based on post-interventional temperature measurements • A 60°C threshold level can be used to predict the ablation zone • The 50°C and 55°C temperature zones tend to overestimate the ablation zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…In both of these cases, researchers used magnetic resonance temperature imaging (MRTI) method to monitor temperature profile during ablation of the respective tissue. In another study, researchers used MR-guided RF ablation of liver tumors and observed increase of temperature ranging from 60-100 °C very near the treatment device in the tumor region during ablation 52 . In microwave treatment of porcine renal cortex experiments, a temperature rise of more than 85 °C at the tip of the antenna was observed 53 .…”
Section: Resultsmentioning
confidence: 99%
“…In both of these cases, researchers used magnetic resonance temperature imaging (MRTI) method to monitor temperature profile during ablation of the respective tissue. In another study, researchers used MR-guided RF ablation of liver tumors and observed increase of temperature ranging from 60-100 °C very near the treatment device in the tumor region during ablation 52 . In microwave treatment of porcine renal cortex experiments, a temperature rise of more than 85 °C at the tip of the antenna was observed 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Dažnai joms gydyti taikoma radijo dažnio abliacija -minimaliai invazyvus audinių suardymo metodas (2)(3)(4)(5). Šio gydymo būdo kol kas negalima pritaikyti visų navikų gydymui ir jis dažniausiai apsiriboja kepenyse, inkstuose, plaučiuose bei kauluose esančiais navikais.…”
Section: įVadasunclassified
“…Apskaičiavus klinikinėje praktikoje padarytų abliacijos zonų matmenų vidurkius, abliacijos zonos dažnai būna apytiksliai 45 x 32 mm dydžio -tokių matmenų abliacijos zoną galima pasiekti naudojant du aplikatorius arba vienu aplikatoriumi sukuriant kelias persidengiančias abliacijos zonas (5). Tyrimais parodyta, kad efektyviau yra naudojant kelis aplikatorius sukurti visą naviką apimančią abliacijos zoną užuot vienu aplikatoriumi kurti kelias persidengiančias abliacijos zonas (29).…”
Section: Bandymų Grupėunclassified
See 1 more Smart Citation
“…thermal conductivity, blood perfusion and heat capacity). For therapeutic applications the objective is to create a substantial temperature increase (to 40-50°C in hyperthermia [1,2] or 75-90°C in thermal ablation [3,4]). …”
Section: Introductionmentioning
confidence: 99%